The reordering of the Batswana Cosmology in the 1840 English-Setswana New Testament - Mothoagae, Itumeleng D. (HTS teologiese studies, 2018)
Ngwao ya Setswana [tradition and customs] has two dimensions: tumelo [belief system] and thuto [education]; it is found in cultural practices and observances such as bogwera [the rite of initiation], letsemma [ploughing], dikgafela [harvesting], bongaka [diviner-healers] and botsetsi ba ntlha le botsetsi jwa bobedi [first menses and first experience of childbirth] to name but a few. These practices were observed through the slaughtering of animals, usually cows, and sheep and were condemned and regarded by missionaries as hindrances to Christianity. Letters to Mahoko a Becwana, a 1883–1896 newspaper, points to the use of biblical scriptures such as 1 Corinthians 10:1–33 by the missionaries to condemn these practices. The 1840 English-Setswana New Testament is a colonial product. Texts such as 1 Corinthians 10:21–22 point to the discursive practice employed by the translator for the purpose of foreignising Setswana cultural concepts, re-domesticating these cultural concepts as new concepts separate from their original meaning and domesticating anglicised concepts. At the centre of the discursive practice, I would argue, are foreignisation, redomestication and domestication. This version of the Bible depicts the impact of colonialism on the cultural practices of the Batswana. The debates in the letters to Mahoko a Becwana, point to the dichotomy of those Batswana who converted to Western colonial Christianity. The debates further depict the choices made by the Batswana when accepting the Christian practices expressed in Western culture, and renouncing all that made them a Motswana. The argument in this article is that in his translation of the Bible into Setswana, Moffat uses ideological strategy as a discursive tool to foreignise and redomesticate the concept of Badimo as a Badimoni [devil] and to domesticate the Western colonial Christian concept of heathen into Setswana vocabulary as baeteni, thus producing a dichotomy within the Batswana. Decolonial and post-colonial translation theories are used as the theoretical framework for this article.